Too TAF Towards the Risk - Stefano Puddu; Andreas Waelchli (University of Neuchâtel, Institute of Economic Research (IRENE), 2011)
During the last financial crisis the Federal Reserve launched several extraordinary actions, including the creation of a number of new facilities for auctioning short-term credit, with the general aim of sustaining the financial sector and of ensuring adequate access to liquidity to financial institutions. One of these programs has been the Term Auction Facility (TAF). The goal of this paper is twofold. First, we want to study banks' liquidity and liability features depending on whether banks received credit from the TAF program. Second, we want to measure the impact of program facilities on banks liquidity risk. In order to achieve these goals we fit a treatment effects model. In the first step the probability of obtaining TAF program facilities has been instrumented by a set of variables measured before the beginning of the TAF program. In the second step, once controlled for potential selection bias and endogeneity, the impact of TAF facilities on banks liquidity risk, posterior to the end of the program, has been measured. The results suggest that, on average, banks that obtained program facilities show higher short term net liabilities, higher volume of short term liabilities and higher short term liabilities over total liabilities. These banks exhibit as well a smaller ratio of short term liabilities over total assets and risk-free assets over short term liabilities. Moreover, it has been found that banks that obtained at some point TAF facilities exhibit smaller ex post liquidity risk as well as that ex ante liquidity risk positively affects the probability of receiving program facilities. Several robustness checks confirm the main results. Our findings support the view point that the Federal Reserve correctly identified the program target banks and it also achieved the goal of decreasing liquidity risk.
Keywords: G21; G28; G32; 330; TAF; Liquidity Risk; Financial Crisis